Analysis of post operation period after primary hip arthroplasty in proximal femoral fracture depending on postsurgery wound drainage - Babalian, Volodymyr (ScienceRise: Medical Science, 2018)
Drainage of postoperative wounds for a long time remained the obligatory stage of operative intervention at arthroplasty of a hip joint. But recently in many clinics there are a tendency for a total refusal from this stage. The results of the research highlight only the positive features of these changes, but our experience has shown both an improvement and a decrease in the outcome of treatment. The aim of the research is to establish the expediency of refusing to drain postoperative wounds after hip replacement with fractures of the proximal thigh. Material and methods. The analysis of 44 patients with fractures of the proximal thigh after the initial replacement with unipolar prothesis with a dual movement head was performed. Representative groups have been formed depending on the use of post-operative wound layer drainage. In the postoperative period, an assessment of pain syndrome for VAS was used. We applied a visual assessment of health (EQ VAS) and questionnaires EQ-5D-5L. Hidden blood loss = BCC x (hematocrit before - hematocrit after), where hematocrit before is the value of the indicator for the operation, hematocrit after - the value of the index for 7 days after the operation. The determination of the volume of circulating blood (BCC) was carried out using the formula by Nadler, Hidalgo and Bloch: PBV=K1×height (m)3+K2×weight (kg)+K3, where K1=0.3669, K2=0.03219, K3=0.6041 for men; K1=0.3561, K2=0.03308, K3=0.1833 for women. Results. The intensification of pain syndrome was detected up to 3 days after the postoperative term in the case of failure of layer drainage. There was no statistically significant difference in the indicators of the quality of life assessment, but the patient’s ability to raise the straightened limb with refusal of drainage was observed more often than 2 days compared with 4 days in patients who performed layered drainage of postoperative wound. Significantly improved hemodynamic rates to 7 days of the postoperative period and consequently reduced blood loss. Twice times more often, hyperemia of the postoperative wound was observed in the event of withdrawal from drainage. Increase the length of the hip circumference and regress to 7 days. According to the assessment of the questionnaire EQ-5D-5L, there was no statistically significant difference in the assessment of the quality of life of the affected, depending on drainage. Conclusions. Denial from drainage improves hemodynamic rates in the postoperative period in the study group, slightly increasing the pain syndrome from the first to the third day. Refusal from the layered drainage of the postoperative wound with the fractures of the proximal thigh section in the primary arthroplasty is reasonable